2017
DOI: 10.5194/cp-13-1791-2017
|View full text |Cite
|
Sign up to set email alerts
|

A multi-proxy analysis of Late Quaternary ocean and climate variability for the Maldives, Inner Sea

Abstract: As a natural sediment trap, the marine sediments of the sheltered central part of the Maldives Inner Sea represent an exceptional archive for paleoenvironmental and climate changes in the equatorial Indian Ocean. To evaluate the complex interplay between high-latitude and monsoonal climate variability, related dust fluxes, and regional oceanographic responses, we focused on Fe / Al, Ti / Al and Si / Ca ratios as proxies for terrigenous sediment delivery and total organic carbon (TOC) and Br XRF counts as proxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 139 publications
(201 reference statements)
3
29
0
Order By: Relevance
“…LGM_glac3% (red), and LGM_all (blue). Triangles show proxy records of quantitative O2 change from (Hoogakker et al, 2015(Hoogakker et al, , 2018Gottschalk et al, 2016;Lu et al, 2016;Bunzel et al, 2017;Umling and Thunell, 2018;Schmiedl and Mackensen, 2006) (Bopp et al, 2013), observed values from WOA2009 (Garcia et al, 2010a) are used for the present. For the LGM simulations, we combine the observed values with the modelled changes.…”
Section: Conclusion and Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…LGM_glac3% (red), and LGM_all (blue). Triangles show proxy records of quantitative O2 change from (Hoogakker et al, 2015(Hoogakker et al, , 2018Gottschalk et al, 2016;Lu et al, 2016;Bunzel et al, 2017;Umling and Thunell, 2018;Schmiedl and Mackensen, 2006) (Bopp et al, 2013), observed values from WOA2009 (Garcia et al, 2010a) are used for the present. For the LGM simulations, we combine the observed values with the modelled changes.…”
Section: Conclusion and Remarksmentioning
confidence: 99%
“…We performed several sensitivity experiments listed in Table 1 to explore the contribution of changes in atmospheric dust and nutrient inventory on glacial carbon and oxygen cycles. Moreover, our modeled oxygen changes are compared to recently reported qualitative (Jaccard and Galbraith, 2012) and quantitative reconstructions (Hoogakker et al, 2015(Hoogakker et al, , 2018Gottschalk et al, 2016;Lu et al, 2016;Bunzel et al, 2017;Umling and Thunell, 2018;Schmiedl and Mackensen, 2006) to evaluate the simulated accumulation of respired carbon. Our simulation show that enhanced efficiency of biological pump associated with glaciogenic dust and increased nutrient inventory plays a crucial role in the glacial CO2 decrease and deep-water deoxygenation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The modern platform configuration was established during the late Middle Miocene at ca 13 Ma with atoll growth paralleled by partial bank drowning and drift deposition (Purdy & Bertram, ; Aubert & Droxler, ; Betzler et al ., , , ; Lüdmann et al ., ). This transition from a sea‐level to current‐controlled system was attributed to the onset and/or intensification of the Indian monsoon (Betzler et al ., , , ,b, ; Lüdmann et al ., ; Bunzel et al ., ; Reolid et al ., ). Since the Middle Miocene the Inner Sea was gradually infilled by ten sequences comprised of delta drifts, elongated mounded drifts and clinoform drift bodies (Lüdmann et al ., , ).…”
Section: General Setting and Backgroundmentioning
confidence: 99%
“…Starting with seismic sequence DS6, at the end of the Messinian, the opening of a southern gateway introduced northward flow of bottom currents into the Inner Sea, resulting in the deposition of giant elongated drifts attached to the eastern flank of the basin, filling it from east to west (Lüdmann et al ., ). Detached drifts form at the downcurrent flanks of the atolls (Betzler et al ., , ) and the currents controlling the drift deposition in the Maldives prevail during the Quaternary (Betzler et al ., ; Bunzel et al ., ; Reolid et al ., ). The water depth at which the drifts were deposited changed through time from ca 50 m at the time of the delta drift deposition (Reolid et al ., ) to ca 500 m in present day (Betzler et al ., ).…”
Section: Introductionmentioning
confidence: 99%